Women’s Empowerment as an Effort to Mitigate Dependence on Online Loans through Strengthening Local-Asset-Based UMKM in Sukagalih Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to reduce women’s dependence on online loans by strengthening local-asset–based micro, small, and medium enterprises (UMKM) in Sukagalih Village using the Asset-Based Community Development (ABCD) approach. Through the stages of discovery, dream, design, deliver, and destiny, the program identified key community assets—such as skills in food processing and sewing, strong PKK networks, and high motivation—to build a foundation for sustainable economic empowerment. Participants collaboratively formulated a vision of achieving financial stability without borrowing, received practical modules on household financial literacy, food-based MSME training, and basic digital marketing, and gained hands-on experience in production, branding, and online promotion. The program outcomes show significant improvements in women’s understanding of financial management, product development skills, digital marketing practices, and confidence to initiate independent economic activities. The formation of a women’s business group and continued mentoring further strengthened social support systems that reduce risky borrowing behavior. Overall, the findings indicate that asset-based empowerment effectively enhances women’s economic resilience and offers a sustainable strategy for mitigating dependence on online loans in rural communities.